Inflammatory impact on tissues surrounding the dental implant of singular abutments bonded onto titanium base - A randomized controlled trial - Chetan Chandra; Rapolu Sisir; Ajith A Chandy; Sharwan K Singh; Jagveer S Saluja; Jeevanandam Loganathan (Wolters Kluwer Medknow Publications, 2023)
Introduction: In dental implants, the biochemical connection between titanium (ti) and bony tissue has been well established. The properties of dental implants such as osseointegration and stability depend upon composition, design of the implant, connection, and design of the abutment, and additional removal of abutments. Recently, laser-generated micro-grooved surface (LSS) and TI abutments are the main focus of preventing peri-implant inflammation. Objectives: To assess the inflammatory impact of singular abutments bonded onto titanium bases on tissues surrounding the dental implant. Methods: Twenty subjects were enrolled. Only those subjects were enrolled who were scheduled to undergo prosthetic rehabilitation of missing teeth. Random division of subjects was done. Group A: Test abutment group and Group B: Control abutment group. The test abutments comprised Computer-Aided Design/Computer-Aided Manufacturing (CAD/CAM) titanium abutments bonded onto titanium abutments. However, control abutments were customized and only one-piece CAD/CAM titanium abutments were enrolled.On 6 months and 12 months of follow-up, the clinical and radiographic examination was done. Assessment of the bone level changes, clinical variables, and IL-1b levels was assessed. Results: Mean IL-1b levels in Group A subjects at baseline, 6 months, and 12 months were 1.52 pg/mL, 1.69 pg/mL, and 1.55 pg/mL, respectively. Mean IL-1b levels among the patients of group B at baseline, 6 months, and 12 months were 1.56 pg/mL, 1.71 pg/mL, and 1.54 pg/mL, respectively. Conclusion: Within the limitation of the study, it can be concluded that the impact on the inflammatory condition of surrounding tissues of dental implant does not vary significantly between single abutments bonded onto Titanium bases and singular abutments.